The columns shipwreck of Kamarina (2nd c. AD) – New data from the Kaukana project, Sicily - Capulli, Massimo (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The shipwreck of the Columns, dated at the end of the 2nd c. AD, lies on a sandy bottom at a depth of 2.5 to 4 m in the bay that opens south of the promontory on which the Syracusans, at the beginning of the 6th century BC, founded the colony of Kamarina. The main cargo consisted of a pair of half-finished columns 80 cm in diameter and approximately 6 m long. The new research on this site, known since the 1970s, is part of an organic program of study of the historical-archaeological evidence preserved along the Ragusa coastline by the University of Udine, in collaboration with the Superintendence of the Sea of Sicily and with the support of the Institute of Nautical Archaeology.